Trees of Amazonian Ecuador: a taxonomically verified species list with data on abundance and distribution - Guevara Andino, Juan (2019)
We compiled a data set for all tree species collected to date in lowland Amazonian Ecuador in order to determine the number of tree species in the region. This data set has been extensively verified by taxonomists and is the most comprehensive attempt to evaluate the tree diversity in one of the richest species regions of the Amazon. We used four main sources of data: mounted specimens deposited in Ecuadorian herbaria only, specimen records of a large-scale 1-hectare-plot network (60 plots in total), data from the Missouri Botanical Garden Tropicos® database (MO), and literature sources. The list of 2,296 tree species names we provide in this data set is based on 47,486 herbarium records deposited in the following herbaria: Alfredo Paredes Herbarium (QAP), Catholic University Herbarium (QCA), Herbario Nacional del Ecuador (QCNE), Missouri Botanical Garden (MO), and records from an extensive sampling of 29,768 individuals with diameter at breast height (dbh) ≥10 cm recorded in our plot network. We also provide data for the relative abundance of species, geographic coordinates of specimens deposited in major herbaria around the world, whether the species is native or endemic, current hypothesis of geographic distribution, representative collections, and IUCN threat category for every species recorded to date in Amazonian Ecuador. These data are described in Metadata S1 and can be used for macroecological, evolutionary, or taxonomic studies. There are no copyright restrictions; data are freely available for noncommercial scientific use (CC BY 3.0). Please see Metadata S1 (Class III, Section B.1: Proprietary restrictions) for additional information on usage.